2012
DOI: 10.1002/chem.201200666
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Organization of Ferrocene–Peptides

Abstract: Hierarchical self-assembly of disubstituted ferrocene (Fc)-peptide conjugates that possess Gly-Val-Phe and Gly-Val-Phe-Phe peptide substituents leads to the formation of nano- and micro-sized assemblies. Hydrogen-bonding and hydrophobic interactions provide directionality to the assembly patterns. The self-assembling behavior of these compounds was studied in solution by using (1)H NMR and circular dichroism (CD) spectroscopies. In the solid state, attenuated total reflectance (ATR) FTIR spectroscopy, single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…S6, ESI † for details). These values are significantly higher than that of other H-bonded Fc-peptide previously reported, 13 suggesting the formation of very strong intermolecular hydrogen bonding interactions. Upon heating the ultrasound-induced gel-phase material all amide protons gradually shift downfield, up to the gel melting temperature of 60 1C (Fig.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…S6, ESI † for details). These values are significantly higher than that of other H-bonded Fc-peptide previously reported, 13 suggesting the formation of very strong intermolecular hydrogen bonding interactions. Upon heating the ultrasound-induced gel-phase material all amide protons gradually shift downfield, up to the gel melting temperature of 60 1C (Fig.…”
contrasting
confidence: 63%
“…Ferrocene (Fc)-peptide conjugates have received significant attention due to their interesting structural properties and their potential bioanalytical applications. [11][12][13] Organogels and hydrogels of Fc-peptide are not common. 14 Recently, the simple conjugate FcCO-Phe-OH has been reported to form a hydrogel.…”
mentioning
confidence: 99%
“…The self-assembly of small molecules in water or in organic solvents could lead to the formation of a gel consisting of a large amount of a solvent entrapped in a three-dimensional (3D) network of nanosized gelator aggregates. Since the aggregates are stabilized by weak noncovalent interactions, various internal or external stimuli (light, sound, pH, solvent, temperature, ions, enzymes) can be used to tune the molecular assembly behavior required for functional expression. It is very difficult to predict the gelling ability of a potential gelator as it is closely related to the 3D intermolecular nature of the gel. Therefore, the design and development of simple and effective gelators that exhibit a sharp and rapidly reversible response to one or more stimuli are rather challenging tasks. Numerous studies on ferrocene-containing peptides have revealed not only the interesting structural properties resulting from the ability of ferrocene scaffolds to undergo turn nucleation but also a potential bioanalytical application. , Recent work on two ferrocene-modified peptides Phe–Phe (FF) and Phe–Tyr (FY) demonstrated that Fc–FF and Fc–FY (Fc = ferrocenoyl) effectively inhibit insulin fibrillation and thus represent an available strategy for the treatment of amyloid aggregation disease …”
Section: Introductionmentioning
confidence: 99%
“…8−11 Numerous studies on ferrocene-containing peptides have revealed not only the interesting structural properties resulting from the ability of ferrocene scaffolds to undergo turn nucleation 12−19 but also a potential bioanalytical application. 20,21 Recent work on two ferrocene-modified peptides Phe−Phe (FF) and Phe−Tyr (FY) demonstrated that Fc−FF and Fc−FY (Fc = ferrocenoyl) effectively inhibit insulin fibrillation and thus represent an available strategy for the treatment of amyloid aggregation disease. 22 Research on ferrocene-containing gelators began with the study of the role of ferrocene in aromatic-mediated intermolecular π interactions in an organogelator consisting of a ferrocene unit linked to a cholesterol group via a short peptide linkage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Ferrocene and its derivatives, because of their lipophilicity, 10,11 excellent electrochemical activity 12,13 and high stability in aqueous solution, 11,14 have received tremendous interest in pharmaceutical chemistry. [15][16][17][18][19][20][21] When incorporated into a drug, the ferrocene moiety could yield interesting results.…”
Section: Introductionmentioning
confidence: 99%